IMPLEMENTASI METODE RATIONAL UNIFIED PROCESS PADA MOBILE DIGITAL LIBRARY - Ependi, Usman; Kunang, Yesi Novaria; Novifika, Seva (JURNAL ILMIAH MATRIK, 2014)
Bina Darma University Library has a large collection of books that are highly qualified. This facility has been used by students to increase knowledge, but there are students who are be lazy to visit the library just to see the collection of books available in the library of the University of Bina Darma. Therefore needed a mobile digital library applications. This application can facilitate student at the University of Bina Darma Palembang in obtaining information about libraries like to see a collection of books and order books anywhere and anytime without having to come Librarianship. Mobile digital library application will use the Rational Unified Process (RUP) as a system development method for building these applications. Of the existing problems, then on to a topic that can be lifted into the discussion with the title "Digital Library Mobile Applications Bina Darma University Palembang Method Using Rational Unified Process (RUP)".